2016
DOI: 10.1142/s1793292016500557
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Specific Activity of Metal Catalysts Toward Oxygen Reduction by Introducing Proton Conductor

Abstract: Enhancing oxygen reduction reaction (ORR) activity and simultaneously reducing usage of noble metal catalysts are signi¯cantly important both in fundamental and applied science communities for polymer electrolyte fuel cells (PEFCs). In this work, we con¯rm the proton conductor (per-°u orosulfonic acid, containing ÀSO 3 H) can promote the speci¯c activity ðI s Þ of metal catalysts toward ORR. Herein, Pt nanoparticles (NPs) with a small and narrow size distribution are encapsulated with per°uorosulfonic acid thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, it is noteworthy that the Pt 4f 7/2 (0) peaks of PFSA-Pt/C@PANI shift to a higher binding energy (72.08 eV) compared with the Pt 4f 7/2 (0) peaks of the commercial Pt/C (71.50 eV) and PFSA-Pt/C (71.88 eV). This shift indicated that there was a reinforced interaction between Pt NPs and C@PANI supports which is responsible for the better stability of PFSA-Pt/C@PANI …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it is noteworthy that the Pt 4f 7/2 (0) peaks of PFSA-Pt/C@PANI shift to a higher binding energy (72.08 eV) compared with the Pt 4f 7/2 (0) peaks of the commercial Pt/C (71.50 eV) and PFSA-Pt/C (71.88 eV). This shift indicated that there was a reinforced interaction between Pt NPs and C@PANI supports which is responsible for the better stability of PFSA-Pt/C@PANI …”
Section: Resultsmentioning
confidence: 98%
“…The trend of the enlarged ECSA of Pt with the addition of PFSA suggests that the PFSA wrapped onto Pt NPs can effectively improve the transfer of reaction species, such as H 2 O and H + , boosting the triple-phase boundary of Pt NPs as reported by our group. 36,37,48 A further investigation into the improvement of ECSA with the introduction of PANI was made by performing N 2 adsorption−desorption isotherms at 77 K. As results, the BET surface area of C@PANI and Vulcan XC-72 carbon black is 78 and 248 m 2 /g, respectively. The pore size analysis reveals the distinct decrease of the surface area after coating PANI, which is mainly caused by the decreased amount of micropores less than 2 nm and partial mesopores ranged from 2.0 to 4.0 nm, as shown in Figure 4b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton exchange membrane fuel cells (PEMFCs) have been attracting a lot of attention as promising energy converters, especially in automobile applications, because of their high efficiency, high energy density, high power density, zero emissions, and rapid cold start-up. Membrane electrode assembly (MEA) as the most important part is the area of electrochemical reaction, especially catalyst layers (CLs) consisting of Pt/C as a catalyst and an electronic conductor, and Nafion as a proton transferred channel to extend the triple-phase boundary (TPB). , Many interfaces are formed during the self-assembly of Pt/C and Nafion due to some physical effects, such as the adsorption between platinum and Nafion, chelation between carbon black and platinum, the interaction between oxygenic groups on the surface of carbon black and Nafion and changes of Nafion structure in the electrocatalytic reaction. These interfaces are also active sites of electrochemical reaction, where catalysts, electron pathway, and proton pathway are simultaneously contained to satisfy the special needs to make the electrochemical reaction. Cheng et al had confirmed that Nafion is able to promote the activity of platinum due to effective proton transfer and improvement of TPB . But the self-assembly of catalyst layer consisted of Pt/C and Nafion is yet to be understood, which plays a vital role to further significantly improve the power density of PEMFC.…”
mentioning
confidence: 99%
“…Cheng et al had confirmed that Nafion is able to promote the activity of platinum due to effective proton transfer and improvement of TPB. 10 But the self-assembly of catalyst layer consisted of Pt/C and Nafion is yet to be understood, which plays a vital role to further significantly improve the power density of PEMFC. In addition, understanding the self-assembly and building the model are important to shed light on proton transfer, electrochemical mechanisms in a polymer electrolyte and the design of novel catalysts and ionomers instead of expensively commercial Pt/C and Nafion, respectively.…”
mentioning
confidence: 99%